CHARGING OF RAILWAY INFRASTRUCTURE OPERATIONAL CAPACITY LIMITATIONS (Perner's Contacts, 2014)
This article deals with in detail about the charging of railway infrastructure operational capacity limitations. It analyses the reasons, discusses about possibilities and reasons of charging or non-charging of operational capacity limitations by individual cases.
Keywords: capacity; infrastructure; charging; payment